Exploring the function of greeting display in a long-term monogamous songbird, the Java sparrow - Yuhan Zhang; Masayo Soma (Animal Cognition)
Abstract Complex displays that comprise multiple behavioral elements play an essential role in the communication of group-living animals. One of them is a greeting display. Greeting is performed during the reunion after a separation, and is known for maintaining social bonds in mammals and pair bonds in monogamous fish. Greeting displays have been documented in birds, but lack functional studies. Java sparrows (Lonchura oryzivora) are gregarious and long-term monogamous songbird species, exhibiting a complex greeting display consisting of a sequence of four repetitive behavioral elements. We hypothesized that Java sparrow greetings function as between-pair communication in social contexts. In particular, we expected that pair-bonded partners would greet more after experiencing longer separation. In addition, we also predicted that they greet more when other conspecific individuals are nearby; as it is more important for them to confirm and advertise their commitment relationships. To test these ideas, we conducted separation-reunion tests using pair-bonded Java sparrows with different separation times (long vs. short) and different social conditions (with vs. without the presence of conspecifics). We calculated and compared the sequential complexity of the greeting displays. We showed that subject pairs performed a greater number of greeting display bouts after longer separation times. In the presence of conspecifics, greeting displays were more frequent, longer, and more complex. Our finding supports the idea that greeting displays in birds are crucial to pair-bond maintenance, contributing to understanding the evolution of complex communications in birds.